Influence of Pregnancy in Multiple Sclerosis and Impact of Disease-Modifying Therapies - Simone, Isabella Laura; Tortorella, Carla; Ghirelli, Alma (Frontiers in Neurology, 2021)
Purpose of this review. This article is a systematic review on the influence pregnancy has on multiple sclerosis and the resulting impact of disease modifying therapies. Findings. Multiple Sclerosis predominantly affects young women with a clinical onset most often during child-bearing age. The impact of multiple sclerosis and disease modifying therapies on fertility, pregnancy, fetal outcome and breastfeeding is a pivotal topic when it comes to clinical practice. The introduction of disease modifying therapies has changed not only the natural history of the disease, but also the perspective of pregnancy in women with multiple sclerosis. Family planning requires careful consideration, especially because many disease modifying drugs are contraindicated during pregnancy. In this article, we review current evidence collected from published literature and drug-specific pregnancy registers on the use of disease modifying therapies. Additionally, we discuss safety profiles for each drug and correlate them to both risk for the exposed fetus and for the mothers interrupting treatments when seeking pregnancy.